Strategi Komunikasi Polres Salatiga Untuk Membangun Kepercayaan Masyarakat - Sanusi, Marchelino; Vanel, Zon (Unitri Press, 2025)
The police play an important role in maintaining security and order and are required to provide professional services. However, public trust in the institution has declined due to various scandals that have tarnished the institution's image. Therefore, an effective communication strategy is needed to rebuild public trust. This study aims to analyze the external communication strategy implemented by Salatiga Police in building a positive image and increasing public trust. The research gap lies in the lack of empirical studies on police communication strategies at the regional level, especially in a small city like Salatiga which has different social characteristics from big cities. This study used a qualitative method with a social phenomenon approach through interview, observation, documentation, and questionnaire techniques. The research subjects included internal elements of Polres Salatiga and the local community, as well as Instagram social media documentation as secondary data. The results show that the external communication strategies include anti-bullying counseling, Operation Zebra Candi, non-standard exhaust raids, morning traffic arrangements, and publication of legal cases through social media and press conferences. These strategies are considered quite effective in increasing public understanding and shaping the professional and transparent image of the Polri institution. Abstrak Polri berperan penting dalam menjaga keamanan dan ketertiban serta dituntut memberikan pelayanan profesional. Namun, kepercayaan publik terhadap institusi ini menurun akibat berbagai skandal yang mencoreng citra institusi. Oleh karena itu, strategi komunikasi yang efektif diperlukan untuk membangun kembali kepercayaan masyarakat. Penelitian ini bertujuan untuk menganalisis strategi komunikasi eksternal yang diterapkan oleh Polres Salatiga dalam membangun citra positif dan meningkatkan kepercayaan publik. Research gap terletak pada minimnya kajian empiris mengenai strategi komunikasi Polri di tingkat kewilayahan, khususnya di kota kecil seperti Salatiga yang memiliki karakteristik sosial yang berbeda dengan kota besar. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomena sosial melalui teknik wawancara, observasi, dokumentasi, dan angket. Subjek penelitian mencakup unsur internal Polres Salatiga dan masyarakat setempat, serta dokumentasi media sosial Instagram sebagai data sekunder. Hasil penelitian menunjukkan bahwa strategi komunikasi eksternal yang dilakukan meliputi penyuluhan anti-perundungan, Operasi Zebra Candi, razia knalpot tidak standar, pengaturan lalu lintas pagi hari, serta publikasi kasus hukum melalui media sosial dan konferensi pers. Strategi ini dinilai cukup efektif dalam meningkatkan pemahaman masyarakat serta membentuk citra profesional dan transparan institusi Polri.